Plastidial (p)ppGpp Synthesis by the Ca2+-Dependent RelA–SpoT Homolog Regulates the Adaptation of Chloroplast Gene Expression to Darkness in Arabidopsis. (22nd October 2020) - Ono, Sumire; Suzuki, Sae; Ito, Doshun; Tagawa, Shota; Shiina, Takashi; Masuda, Shinji
Abstract: In bacteria, the hyper-phosphorylated nucleotide, guanosine 3′, 5′-bis(pyrophosphate) (ppGpp), functions as a secondary messenger under stringent conditions. ppGpp levels are controlled by two distinct enzymes, namely RelA and SpoT, in Escherichia coli . RelA–SpoT homologs (RSHs) are also conserved in plants where they function in the plastids. The model plant Arabidopsis thaliana contains four RSHs: RSH1, RSH2, RSH3 and Ca 2+ -dependent RSH (CRSH). Genetic characterizations of RSH1, RSH2 and RSH3 were undertaken, which showed that the ppGpp-dependent plastidial stringent response significantly influences plant growth and stress acclimation. However, the physiological significance of CRSH-dependent ppGpp synthesis remains unclear, as no crsh -null mutant has been available. Here, to investigate the function of CRSH, a crsh -knockout mutant of Arabidopsis was constructed using a site-specific gene-editing technique, and its phenotype was characterized. A transient increase in ppGpp was observed for 30 min in the wild type (WT) after the light-to-dark transition, but this increase was not observed in the crsh mutant. Similar analyses were performed with the rsh2-rsh3 double and rsh1-rsh2-rsh3 triple mutants and showed that the transient increments of ppGpp in the mutants were higher than those in the WT. The increase in ppGpp in the WT and rsh2 rsh3 accompanied decrements in the mRNA levels of some plastidial genes transcribed by the plastid-encoded plastid RNA polymerase. These results indicate that the transient increase in ppGpp at night is due to CRSH-dependent ppGpp synthesis and that the ppGpp level is maintained by the hydrolytic activities of RSH1, RSH2 and RSH3 to accustom plastidial gene expression to darkness.